Zakat Sebagai Sosial Finansial Untuk Pemberdayaan Masyarakat dan Menanggulangi Kemiskinan (Studi Kasus Pada UPZ di Tasikmalaya) - Mulyadi, Sandi; Abdullah, Muhammad Latif (Mabny: Journal of Sharia Management and Business, 2022)
The aim of this research is to see the optimization of the legality of the Zakat Collecting Unit (UPZ) in Tasikmalaya and to analyze the role of zakat as social finance in helping and empowering the community and in alleviating poverty in the community. The method used is a case study with several UPZ objects in Tasikmalaya. The study found that local governments have not seriously promoted the potential of zakat as evidenced by the absence of zakat regulation by local governments. However, in terms of zakat collection, UPZ has been effective and efficient. Then with regard to community empowerment and poverty alleviation, zakat funds should be allocated for productive and labor-intensive economic activities and make mosques the basis for community empowerment.